Patient perspectives on health care provider practices leading to an axial spondyloarthritis diagnosis: an exploratory qualitative research study - Kate L. Lapane; Catherine Dubé; Katarina Ferrucci; Sara Khan; Kristine A. Kuhn; Esther Yi; Jonathan Kay; Shao-Hsien Liu (BMC Family Practice, 2021)
Abstract Background The average time to a diagnosis for people with axial spondyloarthritis (axSpA) is 7-10 years. Delayed diagnosis may result in increased structural damage, worse physical function, and worse quality of life relative to patients with a timely axSpA diagnosis. Understanding patient experiences may provide insights for how to reduce diagnostic delays. Objective To provide foundational knowledge about patient experiences with healthcare providers leading to an axSpA diagnosis. Methods We conducted an exploratory qualitative research study with six focus groups interviews with participants recruited from three rheumatology clinics within the United States (MA (n = 3); CO (n = 2); PA (n = 1)) that included a total of 26 adults (10 females, 16 males) with rheumatologist confirmed diagnosis of axSpA in 2019. Focus groups were ~ 2 h, audio recorded, transcribed, and subject to dual coding. The codes reviewed were in relation to the patients’ diagnostic experiences. Results Patients described frustrating and lengthy diagnostic journeys. They recognized that the causes of diagnostic delays in axSpA are multifactorial (e.g., no definitive diagnostic test, disease characteristics, lack of primary care provider’s awareness about axSpA, trust). Patients described how doctors minimized or dismissed complaints about symptoms or told them that their issues were psychosomatic. Patients believed the healthcare system contributed to diagnostic delays (e.g., lack of time in clinical visits, difficulty accessing rheumatologists, health insurance challenges). Advice to physicians to reduce the diagnostic delay included allowing time for patients to give a complete picture of their illness experience, listening to, and believing patients, earlier referral to rheumatology, provision of HLA-B27 gene testing, and that physicians need to partner with their patients. Conclusions Patients desire a definitive test that could be administered earlier in the course of axSpA. Until such a test is available, patients want clinicians who listen to, believe, and partner with them, and who will follow them until a diagnosis is reached. Educating primary care clinicians about guidelines and referral for diagnosis of axSpA could reduce diagnostic delay.